Province-wide Adenovirus Type 3 Outbreak with Severe Cases in New Brunswick - Gabriel Girouard; Richard Garceau; Louise Thibault; Christine Bourque; Nathalie Bastien; Yan Li (Canadian Journal of Infectious Diseases and Medical Microbiology)
Adenovirus is a commonly isolated virus in clinical samples. Life-threatening infections, although rare, are described worldwide. An epidemic spread of an adenovirus type 3 strain occurred in the province of New Brunswick during the fall of 2008 to the winter of 2009; it resulted in three severely ill patients, with one fatality. Adenovirus should be considered as a cause of severe community-acquired viral pneumonia, especially when the influenza test is negative.